Project-Based E-LKPD Innovation to Improve the Poetry Writing Ability of Grade 4 Elementary School Students - Nur Samsiyah; Agung Widyantoro; Muhammad Hanif (Journal for Lesson and Learning Studies, 2025)
Poetry writing skills among elementary school students remain relatively low due to limited practice opportunities, insufficient guidance, and a lack of varied learning media, which negatively affect students’ interest and learning motivation. This study aims to analyze learning needs, develop, and examine the effectiveness of a project-based electronic student worksheet (E-LKPD) in improving fourth-grade students’ poetry writing skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included fourth-grade students and teachers as product users. Data were collected through needs analysis questionnaires, interviews, expert validation sheets, teacher and student response questionnaires, and poetry writing skill tests. The research instruments consisted of media and content expert validation sheets, response questionnaires, and learning outcome tests. Data analysis was conducted using descriptive quantitative analysis and inferential statistics, including validity, normality, homogeneity, and effectiveness tests. The results indicate that the project-based E-LKPD demonstrates a very high level of validity, receives positive responses from teachers and students, and is proven effective in improving poetry writing skills in the experimental group compared to the control group. In conclusion, the project-based E-LKPD is feasible for use as a supplementary teaching material and has significant implications for enhancing the quality of poetry writing instruction in elementary education.